2015
DOI: 10.1097/01.sa.0000459249.74578.f8
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum Vitamin D Concentration With Serious Complications After Noncardiac Surgery

Abstract: 2.6%; P = 0.23]). The values decreased after the BCP in the control group, but in the AVP group, 10% decreases were noted with AVP alone and further decreased after the BCP (P < 0.0001). Hypotension occurred less often in the AVP patients than in the control group; 2 patients (13%) in the AVP group and 10 (67%) in the control group required ephedrine (P = 0.003). In the control group, the episodes occurred within 5 minutes of the BCP and lasted 2 to 15 minutes compared with 10 to 15 minutes and 1.5 to 2.5 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
1
10
1
Order By: Relevance
“…LaPar et al [11] reported that, the morbidity and mortality of patients were lowest in patients operated in spring after lung resection and Kestle et al [12] reported that complications such as infection and wound dehiscence were higher in July and August after pediatric shunt surgery. Gruskay et al [13] very similar to our results found that surgical infections decreased to the lowest point in the spring (2.8 %) when compared with summer (4.1 %), less postoperative infection rate (4.6 %) [15]. However, we found no association with vitamin D levels and SSI.…”
Section: Discussionsupporting
confidence: 92%
“…LaPar et al [11] reported that, the morbidity and mortality of patients were lowest in patients operated in spring after lung resection and Kestle et al [12] reported that complications such as infection and wound dehiscence were higher in July and August after pediatric shunt surgery. Gruskay et al [13] very similar to our results found that surgical infections decreased to the lowest point in the spring (2.8 %) when compared with summer (4.1 %), less postoperative infection rate (4.6 %) [15]. However, we found no association with vitamin D levels and SSI.…”
Section: Discussionsupporting
confidence: 92%
“…High vitamin D levels were found to significantly decrease mortality rates. Also, vitamin D concentration was associated with mortality at the hospital, serious infection, and serious cardiovascular events (37). In contrast to these studies, there was no significant relationship between vitamin D levels and APACHE II scores, which indicate mortality, in both groups in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Even if 25‐OH vitamin D is simply a risk marker correlated with causal risk factors, there remains strong interest in whether it can better identify high‐ and low‐risk patients compared to established risk factors. In several prospective cohort studies of postsurgical or intensive care unit patients, 25‐OH vitamin D was inversely associated with late discharge, in‐hospital death, serious infections, disease severity, and secondary CVD events . Furthermore, in a study of 3371 patients undergoing coronary artery bypass grafting or valve surgery, 25‐OH vitamin D was inversely associated with postoperative cardiac complications including in‐hospital death, myocardial infarction, low output syndrome, and stroke .…”
Section: Discussionmentioning
confidence: 99%
“…While several clinical studies have evaluated the association between 25‐OH vitamin D and risk of CVD outcomes, complications, and mortality following surgery or hospitalization, few have fully evaluated the prognostic value of 25‐OH vitamin D by contrasting model discrimination, fit, and calibration to those from models containing established risk factors. Furthermore, none have examined the ability of 25‐OH vitamin D to appropriately reclassify patient risk when added to models containing established risk factors.…”
Section: Introductionmentioning
confidence: 99%